NT-proBNP, C-Reactive Protein and Soluble uPAR in a Bi-Ethnic Male Population: The SAfrEIC Study - Kruger, Ruan (Public Library of Science, 2013)
OBJECTIVE AND DESIGN: This cross-sectional study aimed to investigate associations between a marker of cardiac strain, the N-terminal prohormone B-type natriuretic peptide (NT-proBNP), and inflammation as reflected by either a conventional or novel inflammatory marker in a bi-ethnic South African cohort. METHODS AND SUBJECTS: We measured NT-proBNP, C-reactive protein (CRP) and plasma-soluble urokinase plasminogen activator receptor (suPAR) levels along with conventional biomarkers in black (n = 117) and white (n = 116) men. RESULTS: NT-proBNP, CRP and suPAR levels were higher in black compared to white men. NT-proBNP was significantly associated with both CRP (r = 0.38; p = 0.001) and suPAR (r = 0.42; p<0.001) in black men only. After full adjustment in multiple regression analyses, the above associations of NT-proBNP with CRP (β = 0.199; p = 0.018) and suPAR (β = 0.257; p<0.01) were confirmed in black men. CONCLUSION: These results suggest that a low-grade inflammatory state as reflected by both a conventional and novel marker of inflammation may contribute to higher cardiovascular risk as reflected by the associations obtained with a marker of cardiac strain in black South African men.